Plasma Exchange and Glucocorticoids in Severe ANCA-Associated Vasculitis - Walsh, Michael; Merkel, Peter A; Peh, Chen-Au; Szpirt, Wladimir M; Puéchal, Xavier; Fujimoto, Shouichi; Hawley, Carmel M; Khalidi, Nader; Floßmann, Oliver; Wald, Ron; Girard, Louis P; Levin, Adeera; et al. (The New England journal of medicine, 2020)
Among patients with severe antineutrophil cytoplasmic antibody–associated vasculitis, plasma exchange did not reduce the incidence of death or end-stage kidney disease. A reduced-dose regimen of oral glucocorticoids was noninferior to a standard-dose regimen with respect to death or ESKD.